The PARENTAL INVOLVEMENT IN HOME-BASED ENGLISH LEARNING: A QUALITATIVE STUDY OF SECOND-GRADE STUDENTS IN AN ISLAMIC PRIVATE ELEMENTARY SCHOOL IN NORTH SUMATRA, INDONESIA - Nurasid, Ami; Ramdan, Arfian Hikmat; Yuliyanti, Wan; Khoir, Muhammad Nasrul; Pambudi, Dimas Purbo (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study examines how parents support home-based English language learning (ELL) among second-grade students in an Indonesian Islamic private elementary school. The study addresses the following research questions: (1) How do parents support their children’s English learning at home? (2) What motivates parents to be involved? and (3) What challenges do they encounter in providing support? Adopting a qualitative design, data were collected from 30 parents at SDIT Permata Hati (North Sumatra) through questionnaires, semi-structured interviews with three selected parents, and home-based documentation of learning resources and practices. Thematic analysis revealed three main themes: (a) instrumental and aspirational motivations driving parental involvement, (b) preferred support strategies such as private tutoring, exposure to English digital media, and embedding English in daily routines, and (c) a capability gap characterized by limited time, low English self efficacy, and pedagogical constraints, which led parents to rely heavily on external courses. The findings indicate that although parents hold strong positive attitudes toward English and recognize its importance for future academic and career opportunities, their involvement tends to be indirect and resource-dependent rather than pedagogically informed. These results imply the need for schools and policymakers to develop structured school-to-home support systems, including parent-oriented guidance, practical home-based learning toolkits, and accessible digital resources to empower parents with limited English proficiency. The study is limited by its small sample size and single-site design, which may restrict generalizability. Future research is recommended to explore how socio-cultural factors, parenting styles, and family values mediate parental involvement in diverse educational contexts.